Pengaruh Aplikasi Tiktok Sebagai Media Promosi dan Kualitas Produk Terhadap Keputusan Pembelian Produk Moisturizer The Originote - Ilham Fadhilah; Aulia Azzahra; Erina Haniammaria; Difa Ardiyanti; Risma Ayu Ramadina; Jajat Jatnika; Kurniawati Mulyanti (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This study discusses the relationship between Tiktok as a promotional media and product quality on the purchasing decision of Moisturizer The Originote. The objective of this study is to evaluate the impact of Tiktok promotions and product quality on the purchasing decision of Moisturizer The Originote. The research utilized nonprobability sampling with purposive sampling involving 100 respondents. Data collection was conducted through a questionnaire distributed via Google Forms. Findings from the analysis indicate that Tiktok promotions have a significant positive effect on purchasing decisions (β1 = 0.562, t-value = 7.894, sig < 0.05), while product quality also significantly impacts purchasing decisions (β2 = 0.433, t-value = 6.057, sig < 0.05). Simultaneously, Tiktok promotions and product quality significantly influence purchasing decisions (F-value = 93.952, sig < 0.000), with an R-squared value of 0.660, suggesting that 66.0% of the variation in purchasing decisions for Moisturizer The Originote can be explained by Tiktok promotions and product quality, while the remaining 34.0% is influenced by other factors not included in this study's model.